2021
DOI: 10.1670/20-035
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Ecology of Rhinophrynus dorsalis (Anura: Rhinophrynidae) in México

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Female-biased sexual size dimorphism is common among anurans and has traditionally been attributed to fecundity selection, favoring larger females that can lay more or larger eggs than small females (Han & Fu, 2013;Nali et al, 2014). This hypothesis has been supported by many studies which reported an increase in egg size with body size of the female for many anurans (Başkale et al, 2011;Hughes & Wylie, 2021;Pereira & Maneyro, 2012;Prado & Haddad, 2005;Zhao et al, 2017). Furthermore, sex differences in growth rates and age structures within populations can lead to sexual size dimorphism (Liao & Lu, 2012;Monnet & Cherry, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Female-biased sexual size dimorphism is common among anurans and has traditionally been attributed to fecundity selection, favoring larger females that can lay more or larger eggs than small females (Han & Fu, 2013;Nali et al, 2014). This hypothesis has been supported by many studies which reported an increase in egg size with body size of the female for many anurans (Başkale et al, 2011;Hughes & Wylie, 2021;Pereira & Maneyro, 2012;Prado & Haddad, 2005;Zhao et al, 2017). Furthermore, sex differences in growth rates and age structures within populations can lead to sexual size dimorphism (Liao & Lu, 2012;Monnet & Cherry, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In the African genus Hemisus , for example, the hands and forearms of males seem to secrete a sticky secretion ( Rödel, 2000 ) that may facilitate the amplexus. Other cases such as the North and Central American species Rhinophrynus dorsalis ( Hughes and Wylie, 2021 ) and the Australian Myobatrachus gouldii ( Roberts, 1981 ; Vertucci et al., 2017 ) should be investigated for the possible presence of glands in their skin with adhesive function. It calls attention that all anurans mentioned above, including Dermatonotus muelleri , are fossorial (or semi-fossorial) and live in dry environments.…”
Section: Discussionmentioning
confidence: 99%